Analisis Karakter Cinta Tanah Air Melalui Kegiatan Nguri-Uri Kebudayaan Pada Siswa Kelas IV di SDN Dungus 1 Kediri - Betty Oktavia Rahmayanti (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purposive of this research is to find out the extent of the character of love for one’s country through Nguri-Uri Cultural Activities at SDN Dungus 1. This research uses descriptive qualitative methods. The subjects in this research are class IV students at SDN Dungus 1. Sampling use purposive sampling techniques. The research sample was 4 students consisting of 2 female students and 2 male students. Data collection techniques were carried out through observation, interview, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research show that Nguri-Uri Cultural Activities can instill the character of love for the country quite well because these activities can bring up several indicators of the character of love for the country in students, namely loving Indonesia culture and art, enjoying the diversity of regional languages, preserving Indonesian culture, and being proud of being Indonesian. There are differences between the four subjects in terms of the indicators of liking regional language diversity, namely subjects IJ and ARW fulfill it one the first day, subjects IJ and AR fulfill it on the second day, and subjects AR and MZA fulfill it on the third day.